A natural rubber material with high tear resistance and high resilience and preparation method thereof

By optimizing the process and formula, high tear-resistant and high resilience natural rubber materials are prepared, which solves the problems of cracks, fatigue failure and insufficient antibacterial properties in existing natural rubber products in applications, and achieves high tear resistance of the material. High resilience and high antibacterial properties significantly extend the service life of the water capsule.

CN118791784BActive Publication Date: 2025-02-18DONGGUAN PULUDA ELECTRONICS TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411101141.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-02-18
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

Existing natural rubber products are prone to cracks, fatigue failure and insufficient antibacterial properties in applications, resulting in a short service life.

Method used

By optimizing the process and formula, natural rubber is used as the main rubber, and the reinforcement compounded with white carbon black and carbon black, 2-thiol methylbenzimidazole zinc salt and 4,4'-bis(α, Anti-aging agents combined with α-dimethylbenzyl)diphenylamine, active agents combined with zinc oxide and stearic acid, and imidazole furancarboxylic acid salt polyionic liquid were modified to prepare high tear resistance and high resilience natural Rubber material.

Benefits of technology

This material can meet up to 800 launches in water bags used in toy water guns, with a launch distance of 7-9 meters, which significantly improves the performance and service life of the water bags, and has high antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure WMUMTL3Z30HWFYB9Q7NWEPWL1ST7TTCOU9A4ZBSV
    Figure WMUMTL3Z30HWFYB9Q7NWEPWL1ST7TTCOU9A4ZBSV
Patent Text Reader

Abstract

The invention relates to the field of rubber, in particular to a natural rubber material with high tear resistance and high resilience and a preparation method thereof. Allyl glycidyl ether is used as a monomer and potassium tert-butoxide is used as an initiator. Polyallyl glycidyl ether is prepared as an unsaturated polyether skeleton by anionic ring-opening polymerization, sulfonic acid anion groups and thiolated nano zinc oxide are sequentially introduced into side chains by mercapto-ene click reaction to obtain polyether anion-modified zinc oxide, and furan carboxylic acid imidazolate polyionic liquid is introduced on the surface of the polyether anion-modified zinc oxide by electrostatic assembly to obtain composite zinc oxide; furan carboxylic acid imidazolate polyionic liquid is used to wet-modify a reinforcing agent, and the furan carboxylic acid imidazolate polyionic liquid is loaded on the surface of the reinforcing agent by controlling the mass ratio thereof, thereby reducing the polarity of the surface thereof, improving the uniformity of the dispersion of the reinforcing agent in the rubber matrix, and improving the mechanical properties of the rubber material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber, in particular to a natural rubber material with high tear resistance and high resilience and a preparation method thereof. Background Art

[0002] Among various toy water guns on the market, the water bag is an important component of the toy water gun. The quality of the water bag is closely related to the performance and service life of the toy water gun. When the water bag is used in a toy water gun, a water pump is used to suck water into the water gun, and the water bag is expanded to 2-3 times of its initial size, and then the water is sprayed out using elasticity. Therefore, the water bag needs to have good tear resistance and resilience. The current market mostly uses rubber as the raw material for making water bags.

[0003] Natural rubber is the most widely used general-purpose rubber. Among rubbers used in water bags, how to solve problems such as crack generation, fatigue failure, and antibacterial properties of rubber products and improve the durability and service life of rubber products is a hot topic in this field. Summary of the invention

[0004] The object of the present invention is to provide a natural rubber material with high tear resistance and high resilience and a preparation method thereof, so as to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a natural rubber material with high tear resistance and high resilience comprises the following steps:

[0007] The natural rubber is put into an internal mixer, and then an activator, an antioxidant, a reinforcing agent, and paraffin oil are added in sequence, mixed, poured out, and tableted with an open mixer, cooled, and left to stand. Then, dispersed sulfur, an accelerator, and a silane coupling agent are added, filtered with a 40-80 mesh filter, tableted, left to stand, and vulcanized to obtain a natural rubber material with high tear resistance and high resilience.

[0008] Furthermore, the raw materials of the natural rubber material are, by weight: 100 parts of natural rubber, 6 parts of activator, 18-30 parts of reinforcing agent, 4-10 parts of paraffin oil, 2-4 parts of antioxidant, 1.5-2.5 parts of dispersed sulfur, 1.1-2 parts of accelerator, and 1-2 parts of silane coupling agent.

[0009] Furthermore, the working conditions of the static treatment are: temperature of 20-35°C and time of 7-9h.

[0010] Furthermore, the working conditions of vulcanization are: temperature of 20-35°C, time of 3-5min, and pressure of 8-9MPa.

[0011] Furthermore, the antioxidant is prepared by mixing 2-thiol methylbenzimidazole zinc salt and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine in a mass ratio of 1:1.

[0012] Furthermore, the accelerator is a mixture of a thiuram accelerator and a sulfonamide accelerator in a mass ratio of (0.1-0.5): (1-1.5).

[0013] Furthermore, the reinforcing agent is obtained by compounding white carbon black and carbon black in a mass ratio of 2:1.

[0014] Furthermore, the active agent is a compound of zinc oxide and stearic acid in a mass ratio of 5:1.

[0015] Further, the reinforcing agent is modified, comprising the following steps:

[0016] The reinforcing agent and ethanol are mixed, ultrasonically dispersed for 20-30 minutes, furan carboxylic acid imidazolium salt polyionic liquid is added, stirred at 18-35° C. for 2-3 hours, washed and dried to obtain a modified reinforcing agent.

[0017] Furthermore, the mass ratio of the reinforcing agent to the furancarboxylic acid imidazolium salt polyionic liquid is 15:4.

[0018] Furthermore, the active agent is a composite zinc oxide and stearic acid compounded in a mass ratio of 5:1. The preparation of the composite zinc oxide includes the following steps:

[0019] (1) Anhydrous ethanol and deionized water are mixed, nano zinc oxide is added, and ultrasonic treatment is performed for 20-30 minutes. A mixed solution of 3-mercaptopropyltriethoxysilane and anhydrous ethanol is added, and the temperature is raised to 45-55° C. and kept warm for 5-6 hours. The mixture is washed and dried to obtain thiolated nano zinc oxide;

[0020] (2) Under a nitrogen atmosphere, tetrahydrofuran, allyl glycidyl ether and potassium tert-butoxide are mixed, stirred in an oil bath at 58-62°C for 18-20 hours, hydrochloric acid is added, filtered, dialyzed in deionized water and ethanol in turn, and rotary evaporated to obtain an unsaturated polyether skeleton;

[0021] (3) Mixing terpyridinium chloride hexahydrate, p-toluidine, and N-methylpyrrolidone, adding an unsaturated polyether skeleton and sodium 3-mercapto-1-propanesulfonate, irradiating with light at a wavelength of 450 nm for 7-8 hours, and then dialyzing alternately in deionized water and ethanol, and rotary evaporating to obtain an intermediate preparation; mixing terpyridinium chloride hexahydrate, p-toluidine, and N-methylpyrrolidone, adding the intermediate preparation and thiolated nano zinc oxide, irradiating with light at a wavelength of 450 nm for 7-8 hours, dialyzing in ethanol, and rotary evaporating to obtain polyether anion modified zinc oxide;

[0022] (4) The polyether anion modified zinc oxide, furan carboxylic acid imidazolium salt polyionic liquid and N-methylpyrrolidone are mixed, ultrasonically stirred for 20-30 minutes, and then kept at 18-25° C. for 2-3 hours, and rotary evaporated to obtain composite zinc oxide.

[0023] Furthermore, the preparation of furancarboxylic acid imidazolium salt polyionic liquid includes the following steps: under nitrogen protection, 1-vinyl-3-ethylimidazolium bromide, azobisisobutyronitrile and methanol are mixed, the temperature is raised to 58-62°C and kept warm for 11-12 hours, transferred to acetone, filtered, a mixed solution of N,N-dimethylformamide and 5-((3,5-dimethyl-1H-pyrazol-1-yl)methyl)furan-2-carboxylate sodium is added, dialyzed with deionized water for 24 hours, and freeze-dried to obtain furancarboxylic acid imidazolium salt polyionic liquid.

[0024] Beneficial effects of the present invention:

[0025] The present invention provides a natural rubber material with high tear resistance and high resilience and a preparation method thereof. Through process and formula optimization, a natural rubber material with high tear resistance, high resilience and high antibacterial properties is prepared, and is applied to a water bag of a toy water gun. After being installed and tested, it can meet up to 800 launches with a launch distance of 7-9 meters, which can greatly improve the performance and service life of the water bag.

[0026] In the present invention, natural rubber is used as the main rubber. Based on the requirements of high tear and high rebound of the material, white carbon black and carbon black are selected as reinforcing agents, dispersed sulfur is used as a vulcanizing agent, and in order to improve its service life, 2-thiol methylbenzimidazole zinc salt and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine are selected as antioxidants in a mass ratio of 1:1, a certain amount of paraffin oil is added to adjust the hardness of the material, and zinc oxide and stearic acid are selected as active agents in a mass ratio of 5:1.

[0027] Zinc oxide is one of the most widely used additives in rubber products. It is not only used as an activator for rubber vulcanization, but also can improve the heat resistance, antibacterial properties and thermal conductivity of rubber. However, zinc is a heavy metal. With the increasing environmental protection requirements, it is imperative to reduce the amount of zinc used in rubber products. Therefore, in the present invention, allyl glycidyl ether is used as a monomer and potassium tert-butoxide is used as an initiator. Polyallyl glycidyl ether is prepared as an unsaturated polyether skeleton by anionic ring-opening polymerization. Sulfonic acid anion groups and thiolated nano zinc oxide are introduced into the side chain in sequence by thiol-ene click reaction to obtain polyether anion-modified zinc oxide, wherein the thiolated nano zinc oxide is modified by using 3-mercaptopropyltriethoxysilane to significantly improve the nano zinc oxide. The uniformity of zinc dispersion in the rubber material improves its activation effect, while greatly improving its extraction resistance and extending the service life of the rubber; at the same time, through electrostatic assembly, furan carboxylic acid imidazolate polyionic liquid is introduced on the surface of polyether anion modified zinc oxide; wherein the furan carboxylic acid imidazolate polyionic liquid is 1-vinyl-3-ethylimidazolium bromide polymerized under the action of azobisisobutyronitrile, and then ion exchanged with 5-((3,5-dimethyl-1H-pyrazol-1-yl)methyl)furan-2-carboxylate sodium to generate an imidazolate polyionic liquid with a furan structure, which greatly improves the thermal stability and antibacterial properties of the material, enhances the complexity of the cross-linking network in the material, improves the material's resistance to mechanical damage, and improves the material's shape memory ability.

[0028] In order to solve the problems that a large number of hydroxyl groups exist on the surface of the reinforcing agent, it is difficult to disperse evenly in the rubber matrix, and the processing performance of white carbon black is poor, it is difficult to eat the material, and it is easy to cause dust pollution. In the present invention, furan carboxylic acid imidazolium salt polyionic liquid is used to wet-modify the reinforcing agent. By controlling its mass ratio, the furan carboxylic acid imidazolium salt polyionic liquid is loaded on the surface of the reinforcing agent, the polarity of its surface is reduced, the uniformity of the dispersion of the reinforcing agent in the rubber matrix is ​​improved, the mechanical properties of the rubber material are improved, and thus the antibacterial property and mechanical damage resistance of the material are improved. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0031] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0032] Embodiment 1: A method for preparing a natural rubber material with high tear resistance and high resilience, comprising the following steps:

[0033] The natural rubber is put into an internal mixer, and then an activator, an antioxidant, a reinforcing agent, and paraffin oil are added in sequence, mixed, poured out, and tableted with an open mixer, cooled, and left to stand, and then dispersed sulfur, an accelerator, and a silane coupling agent are added, filtered with a 60-mesh filter, tableted, left to stand, and vulcanized to obtain a natural rubber material with high tear resistance and high resilience;

[0034] The raw materials of the natural rubber material are as follows, by weight: 100 parts of natural rubber, 6 parts of active agent, 25 parts of reinforcing agent, 7 parts of paraffin oil, 3 parts of antioxidant, 2 parts of dispersed sulfur, 1.7 parts of accelerator, and 1.5 parts of silane coupling agent;

[0035] The working conditions for static treatment are: temperature 30℃, time 8h; the working conditions for vulcanization are: temperature 30℃, time 4min, pressure 8.5MPa;

[0036] The antioxidant is prepared by mixing 2-thiol methylbenzimidazole zinc salt and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine in a mass ratio of 1:1; the accelerator is prepared by mixing thiuram accelerator and sulfonamide accelerator in a mass ratio of 0.3:1.4; the reinforcing agent is prepared by mixing white carbon black and carbon black in a mass ratio of 2:1;

[0037] The active agent is prepared by mixing zinc oxide and stearic acid in a mass ratio of 5:1.

[0038] Embodiment 2: A method for preparing a natural rubber material with high tear resistance and high resilience, comprising the following steps:

[0039] The natural rubber is put into an internal mixer, and then an activator, an antioxidant, a reinforcing agent, and paraffin oil are added in sequence, mixed, poured out, and tableted with an open mixer, cooled, and left to stand, and then dispersed sulfur, an accelerator, and a silane coupling agent are added, filtered with a 40-mesh filter, tableted, left to stand, and vulcanized to obtain a natural rubber material with high tear resistance and high resilience;

[0040] The raw materials of the natural rubber material are as follows, by mass: 100 parts of natural rubber, 6 parts of active agent, 18 parts of reinforcing agent, 4 parts of paraffin oil, 2 parts of antioxidant, 1.5 parts of dispersed sulfur, 1.1 parts of accelerator, and 1 part of silane coupling agent;

[0041] The working conditions for static treatment are: temperature 20℃, time 9h; the working conditions for vulcanization are: temperature 2℃, time 3min, pressure 8MPa;

[0042] The antioxidant is prepared by mixing 2-thiol methylbenzimidazole zinc salt and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine in a mass ratio of 1:1; the accelerator is prepared by mixing thiuram accelerator and sulfonamide accelerator in a mass ratio of 0.1:1; the reinforcing agent is prepared by mixing white carbon black and carbon black in a mass ratio of 2:1;

[0043] The reinforcing agent is modified, comprising the following steps:

[0044] 30 g of reinforcing agent and 400 mL of ethanol were mixed, ultrasonically dispersed for 20 min, 8 g of furan carboxylic acid imidazolium salt polyionic liquid was added, stirred at 18 °C for 3 h, washed and dried to obtain a modified reinforcing agent;

[0045] The active agent is a composite zinc oxide and stearic acid mixed in a mass ratio of 5:1. The preparation of the composite zinc oxide includes the following steps:

[0046] (1) 30 mL of anhydrous ethanol and 10 mL of deionized water were mixed, 2 g of nano zinc oxide was added, and ultrasonic treatment was performed for 20 min. A mixture of 2 mL of 3-mercaptopropyltriethoxysilane and 10 mL of anhydrous ethanol was added, and the temperature was raised to 45 ° C and kept for 6 h. The mixture was washed and dried to obtain thiolated nano zinc oxide;

[0047] (2) Under a nitrogen atmosphere, 30 mL of tetrahydrofuran, 48 mL of allyl glycidyl ether, and 24 mL of potassium tert-butoxide were mixed, stirred in an oil bath at 58°C for 20 h, 3 mL of 2% hydrochloric acid was added, filtered, dialyzed in deionized water and ethanol in turn, and rotary evaporated to obtain an unsaturated polyether skeleton;

[0048] (3) 14.4 mg of terpyridyl ruthenium chloride hexahydrate, 0.14 mg of p-toluidine, and 24 mL of N-methylpyrrolidone were mixed, 4 g of unsaturated polyether skeleton and 1.72 g of sodium 3-mercapto-1-propanesulfonate were added, and light with a wavelength of 450 nm was irradiated for 7 h, and then dialyzed alternately in deionized water and ethanol, and rotary evaporated to obtain an intermediate preparation; 3.6 mg of terpyridyl ruthenium chloride hexahydrate, 37 mg of p-toluidine, and 6 mL of N-methylpyrrolidone were mixed, 1 g of the intermediate preparation and 0.43 g of thiolated nano zinc oxide were added, and light with a wavelength of 450 nm was irradiated for 7 h, and then dialyzed in ethanol and rotary evaporated to obtain polyether anion modified zinc oxide;

[0049] (4) 3 g of polyether anion-modified zinc oxide, 4 g of furan carboxylic acid imidazolium salt polyionic liquid, and 15 mL of N-methylpyrrolidone were mixed, ultrasonically stirred for 20 min, and then kept at 18 ° C for 3 h, and rotary evaporated to obtain composite zinc oxide;

[0050] The preparation of furancarboxylic acid imidazolium salt polyionic liquid comprises the following steps: under nitrogen protection, 40mmol 1-vinyl-3-ethylimidazolium bromide, 0.06g azobisisobutyronitrile and 40mL methanol are mixed, the temperature is raised to 58°C and kept warm for 12h, the mixture is transferred to 100mL acetone, filtered, 60mL N,N-dimethylformamide and 40mmol sodium 5-((3,5-dimethyl-1H-pyrazol-1-yl)methyl)furan-2-carboxylate are added, the mixture is dialyzed with deionized water for 24h, and freeze-dried to obtain furancarboxylic acid imidazolium salt polyionic liquid.

[0051] Embodiment 3: A method for preparing a natural rubber material with high tear resistance and high resilience, comprising the following steps:

[0052] The natural rubber is put into an internal mixer, and then an activator, an antioxidant, a reinforcing agent, and paraffin oil are added in sequence, mixed, poured out, and tableted with an open mixer, cooled, and left to stand, and then dispersed sulfur, an accelerator, and a silane coupling agent are added, filtered with a 60-mesh filter, tableted, left to stand, and vulcanized to obtain a natural rubber material with high tear resistance and high resilience;

[0053] The raw materials of the natural rubber material are as follows, by weight: 100 parts of natural rubber, 6 parts of active agent, 25 parts of reinforcing agent, 7 parts of paraffin oil, 3 parts of antioxidant, 2 parts of dispersed sulfur, 1.7 parts of accelerator, and 1.5 parts of silane coupling agent;

[0054] The working conditions for static treatment are: temperature 30℃, time 8h; the working conditions for vulcanization are: temperature 30℃, time 4min, pressure 8.5MPa;

[0055] The antioxidant is prepared by mixing 2-thiol methylbenzimidazole zinc salt and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine in a mass ratio of 1:1; the accelerator is prepared by mixing thiuram accelerator and sulfonamide accelerator in a mass ratio of 0.3:1.4; the reinforcing agent is prepared by mixing white carbon black and carbon black in a mass ratio of 2:1;

[0056] The reinforcing agent is modified, comprising the following steps:

[0057] 30 g of reinforcing agent and 400 mL of ethanol were mixed, ultrasonically dispersed for 25 min, 8 g of furan carboxylic acid imidazolium salt polyionic liquid was added, stirred at 20° C. for 2.5 h, washed and dried to obtain a modified reinforcing agent;

[0058] The active agent is a composite zinc oxide and stearic acid mixed in a mass ratio of 5:1. The preparation of the composite zinc oxide includes the following steps:

[0059] (1) 30 mL of anhydrous ethanol and 10 mL of deionized water were mixed, 2 g of nano zinc oxide was added, and ultrasonic treatment was performed for 25 min. A mixed solution of 2 mL of 3-mercaptopropyltriethoxysilane and 10 mL of anhydrous ethanol was added, and the temperature was raised to 50 ° C and kept for 5.5 h. The mixture was washed and dried to obtain thiolated nano zinc oxide.

[0060] (2) Under a nitrogen atmosphere, 30 mL of tetrahydrofuran, 48 mL of allyl glycidyl ether, and 24 mL of potassium tert-butoxide were mixed, stirred in an oil bath at 60°C for 19 h, 3 mL of 2% hydrochloric acid was added, the mixture was filtered, and the mixture was dialyzed in deionized water and ethanol in turn, and rotary evaporated to obtain an unsaturated polyether skeleton;

[0061] (3) 14.4 mg of terpyridyl ruthenium chloride hexahydrate, 0.14 mg of p-toluidine, and 24 mL of N-methylpyrrolidone were mixed, 4 g of unsaturated polyether skeleton and 1.72 g of sodium 3-mercapto-1-propanesulfonate were added, and light with a wavelength of 450 nm was irradiated for 7.5 h, and then dialyzed alternately in deionized water and ethanol, and rotary evaporated to obtain an intermediate preparation; 3.6 mg of terpyridyl ruthenium chloride hexahydrate, 37 mg of p-toluidine, and 6 mL of N-methylpyrrolidone were mixed, 1 g of the intermediate preparation and 0.43 g of thiolated nano zinc oxide were added, and light with a wavelength of 450 nm was irradiated for 7.5 h, and then dialyzed in ethanol and rotary evaporated to obtain polyether anion modified zinc oxide;

[0062] (4) 3 g of polyether anion-modified zinc oxide, 4 g of furan carboxylic acid imidazolium salt polyionic liquid, and 15 mL of N-methylpyrrolidone were mixed, ultrasonically stirred for 25 min, then kept at 20 ° C for 2.5 h, and rotary evaporated to obtain composite zinc oxide;

[0063] The preparation of furancarboxylic acid imidazolium salt polyionic liquid comprises the following steps: under nitrogen protection, 40mmol 1-vinyl-3-ethylimidazolium bromide, 0.06g azobisisobutyronitrile and 40mL methanol are mixed, the temperature is raised to 60°C and kept for 11.5h, the mixture is transferred to 100mL acetone, filtered, 60mL N,N-dimethylformamide and 40mmol sodium 5-((3,5-dimethyl-1H-pyrazol-1-yl)methyl)furan-2-carboxylate are added, the mixture is dialyzed with deionized water for 24h, and freeze-dried to obtain furancarboxylic acid imidazolium salt polyionic liquid.

[0064] Embodiment 4: A method for preparing a natural rubber material with high tear resistance and high resilience, comprising the following steps:

[0065] The natural rubber is put into an internal mixer, and then an activator, an antioxidant, a reinforcing agent, and paraffin oil are added in sequence, mixed, poured out, and tableted with an open mixer, cooled, and left to stand, and then dispersed sulfur, an accelerator, and a silane coupling agent are added, filtered with an 80-mesh filter, tableted, left to stand, and vulcanized to obtain a natural rubber material with high tear resistance and high resilience;

[0066] The raw materials of the natural rubber material are as follows, by weight: 100 parts of natural rubber, 6 parts of active agent, 30 parts of reinforcing agent, 10 parts of paraffin oil, 4 parts of antioxidant, 2.5 parts of dispersed sulfur, 2 parts of accelerator, and 2 parts of silane coupling agent;

[0067] The working conditions for static treatment are: temperature 35℃, time 7h; the working conditions for vulcanization are: temperature 35℃, time 5min, pressure 8MPa;

[0068] The antioxidant is prepared by mixing 2-thiol methylbenzimidazole zinc salt and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine in a mass ratio of 1:1; the accelerator is prepared by mixing thiuram accelerator and sulfonamide accelerator in a mass ratio of 0.5:1.5; the reinforcing agent is prepared by mixing white carbon black and carbon black in a mass ratio of 2:1;

[0069] The reinforcing agent is modified, comprising the following steps:

[0070] 30 g of reinforcing agent and 400 mL of ethanol were mixed, ultrasonically dispersed for 30 min, 8 g of furan carboxylic acid imidazolium salt polyionic liquid was added, stirred at 35 ° C for 2 h, washed and dried to obtain a modified reinforcing agent;

[0071] The active agent is a composite zinc oxide and stearic acid mixed in a mass ratio of 5:1. The preparation of the composite zinc oxide includes the following steps:

[0072] (1) 30 mL of anhydrous ethanol and 10 mL of deionized water were mixed, 2 g of nano zinc oxide was added, and ultrasonic treatment was performed for 30 min. A mixture of 2 mL of 3-mercaptopropyltriethoxysilane and 10 mL of anhydrous ethanol was added, and the temperature was raised to 55 ° C and kept for 5 h. The mixture was washed and dried to obtain thiolated nano zinc oxide.

[0073] (2) Under a nitrogen atmosphere, 30 mL of tetrahydrofuran, 48 mL of allyl glycidyl ether, and 24 mL of potassium tert-butoxide were mixed, stirred in an oil bath at 62°C for 18 h, 3 mL of 2% hydrochloric acid was added, the mixture was filtered, and the mixture was dialyzed in deionized water and ethanol in turn, and rotary evaporated to obtain an unsaturated polyether skeleton;

[0074] (3) 14.4 mg of terpyridyl ruthenium chloride hexahydrate, 0.14 mg of p-toluidine, and 24 mL of N-methylpyrrolidone were mixed, 4 g of unsaturated polyether skeleton and 1.72 g of sodium 3-mercapto-1-propanesulfonate were added, and light with a wavelength of 450 nm was irradiated for 8 h, and then dialyzed alternately in deionized water and ethanol, and rotary evaporated to obtain an intermediate preparation; 3.6 mg of terpyridyl ruthenium chloride hexahydrate, 37 mg of p-toluidine, and 6 mL of N-methylpyrrolidone were mixed, 1 g of the intermediate preparation and 0.43 g of thiolated nano zinc oxide were added, and light with a wavelength of 450 nm was irradiated for 8 h, and then dialyzed in ethanol and rotary evaporated to obtain polyether anion modified zinc oxide;

[0075] (4) 3 g of polyether anion-modified zinc oxide, 4 g of furan carboxylic acid imidazolium salt polyionic liquid, and 15 mL of N-methylpyrrolidone were mixed, ultrasonically stirred for 30 min, then kept at 25 °C for 2 h, and rotary evaporated to obtain composite zinc oxide;

[0076] The preparation of furancarboxylic acid imidazolium salt polyionic liquid comprises the following steps: under nitrogen protection, 40mmol 1-vinyl-3-ethylimidazolium bromide, 0.06g azobisisobutyronitrile and 40mL methanol are mixed, the temperature is raised to 62°C and kept warm for 11h, the mixture is transferred to 100mL acetone, filtered, 60mL N,N-dimethylformamide and 40mmol sodium 5-((3,5-dimethyl-1H-pyrazol-1-yl)methyl)furan-2-carboxylate are added, the mixture is dialyzed with deionized water for 24h, and freeze-dried to obtain furancarboxylic acid imidazolium salt polyionic liquid.

[0077] Comparative Example 1: Taking Example 4 as the control group, nano zinc oxide was used to replace the composite zinc oxide, and the other processes were normal.

[0078] Comparative Example 2: Example 4 was used as a control group, the reinforcing agent was not modified, and other processes were normal.

[0079] Comparative Example 3: Example 4 was used as a control group, furancarboxylic acid imidazolium salt polyionic liquid was not prepared, and other processes were normal.

[0080] Sources of raw materials used (for demonstration purposes only):

[0081] Natural rubber SVR3L: Made in Vietnam; Stearic acid 1801: Made in Indonesia; Paraffin oil: Ningbo Hansheng Chemical Co., Ltd.; 2-Mercaptomethylbenzimidazole zinc salt ZMTI: Hebi Yuanhao New Materials Group Co., Ltd.; 4,4'-bis(α,α-dimethylbenzyl)diphenylamine 10081-67-1: Hubei Nona Technology Co., Ltd.; Dispersed sulfur S-80GE, silane coupling agent Si-69-50GE, thiuram accelerator TBZTD, sulfonamide accelerator CBS: Jiangsu Ruiba New Materials Technology Co., Ltd.; White carbon black ULTRASIL® VN3 / GR: EVONIK; Carbon black N330: Germany Orion; 5-((3,5-dimethyl-1H-pyrazol-1-yl)methyl )Sodium furan-2-carboxylate 1147196-77-7: Nanjing Shizhou Biotechnology Co., Ltd.; Nano zinc oxide Z141332, stearic acid S432958, 3-mercaptopropyltriethoxysilane M158078, tetrahydrofuran T103263, allyl glycidyl ether A106314, potassium tert-butoxide P111076, terpyridinium chloride hexahydrate ruthenium T113540, p-toluidine T108450, N-methylpyrrolidone M100589, sodium 3-mercapto-1-propanesulfonate S106463, 1-vinyl-3-ethylimidazole bromide E588795, azobisisobutyronitrile A434183: Aladdin reagent; ethanol, hydrochloric acid, methanol, acetone, analytical grade: Sinopharm reagent.

[0082] Performance test: The rubber materials prepared in the examples and comparative examples were tested:

[0083] Tensile strength: measured with reference to ASTM D412, the sample was cut into a dumbbell of type 1, and the tensile speed of the tensile testing machine was 500 mm / min; Tear strength: measured with reference to ASTM D624, using type A sample, and the speed of the testing machine was 500 mm / min; Rebound resilience: measured with reference to ASTM D7121; Antibacterial property: Staphylococcus aureus was used as the test strain, and the plate method was used for testing; the results are shown in Table 1 below;

[0084] Table 1

[0085]

[0086] The present invention provides a natural rubber material with high tear resistance and high resilience and a preparation method thereof. Through process and formula optimization, a natural rubber material with high tear resistance, high resilience and high antibacterial properties is prepared, so that the natural rubber material can be applied to a water bag of a toy water gun to greatly extend the service life of the water bag. In Table 1, / indicates that the item has not been tested.

[0087] By comparing Example 4 with Comparative Examples 1 and 3, it can be seen that zinc oxide, as one of the most widely used additives in rubber products, is not only used as an activator for rubber vulcanization, but also can improve the heat resistance, antibacterial properties and thermal conductivity of rubber. However, zinc is a heavy metal. With the increasing environmental protection requirements, it is imperative to reduce the amount of zinc used in rubber products. Therefore, in the present invention, allyl glycidyl ether is used as a monomer and potassium tert-butoxide is used as an initiator. Polyallyl glycidyl ether is prepared as an unsaturated polyether skeleton by anionic ring-opening polymerization, and sulfonic acid anion groups and thiolated nano zinc oxide are sequentially introduced into the side chain by thiol-ene click reaction to obtain polyether anion-modified zinc oxide, wherein the thiolated nano zinc oxide is prepared by 3-mercaptopropyltriethoxysilane on nano zinc oxide. Modification can greatly improve the uniformity of dispersion of nano zinc oxide in rubber materials, improve its activation effect, and at the same time greatly improve its extraction resistance, thereby extending the service life of the rubber; at the same time, furan carboxylic acid imidazolate polyionic liquid is introduced on the surface of polyether anion modified zinc oxide through electrostatic assembly; wherein the furan carboxylic acid imidazolate polyionic liquid is 1-vinyl-3-ethylimidazolium bromide polymerized under the action of azobisisobutyronitrile, and then ion exchanged with sodium 5-((3,5-dimethyl-1H-pyrazol-1-yl)methyl)furan-2-carboxylate to generate an imidazolate polyionic liquid with a furan structure, which greatly improves the thermal stability and antibacterial properties of the material, enhances the complexity of the cross-linking network in the material, improves the material's resistance to mechanical damage, and improves the material's shape memory ability.

[0088] By comparing Example 4 with Comparative Examples 2 and 3, it can be seen that in order to solve the problems that a large number of hydroxyl groups exist on the surface of the reinforcing agent white carbon black, it is difficult to disperse in the rubber matrix, and the white carbon black has poor processing performance, is difficult to eat, and is easy to cause dust pollution, etc., the present invention adopts furan carboxylic acid imidazolate salt polyionic liquid to wet-modify the reinforcing agent, and by controlling its mass ratio, the furan carboxylic acid imidazolate salt polyionic liquid is loaded on the surface of the reinforcing agent, thereby reducing its surface polarity, improving the uniformity of the dispersion of the reinforcing agent in the rubber matrix, and improving the mechanical properties of the rubber material; thereby improving the antibacterial property and mechanical damage resistance of the material.

[0089] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a natural rubber material with high tear resistance and high resilience, characterized in that: The following steps are involved: The natural rubber is put into an internal mixer, and then an activator, an antioxidant, a reinforcing agent, and paraffin oil are added in sequence, mixed, poured out, and tableted with an open mixer, cooled, and left to stand, and then dispersed sulfur, an accelerator, and a silane coupling agent are added, filtered with a 40-80 mesh filter, tableted, left to stand, and vulcanized to obtain a natural rubber material with high tear resistance and high resilience; The reinforcing agent is prepared by mixing white carbon black and carbon black in a mass ratio of 2:1; The reinforcing agent is modified, comprising the following steps: The reinforcing agent and ethanol are mixed, ultrasonically dispersed for 20-30 minutes, furan carboxylic acid imidazolium salt polyionic liquid is added, stirred at 18-35° C. for 2-3 hours, washed and dried to obtain a modified reinforcing agent; The preparation of the furan carboxylic acid imidazolium salt polyionic liquid comprises the following steps: under nitrogen protection, 1-vinyl-3-ethylimidazolium bromide, azobisisobutyronitrile and methanol are mixed, the temperature is raised to 58-62° C. and kept warm for 11-12 hours, the mixture is transferred to acetone, filtered, a mixed solution of N,N-dimethylformamide and sodium 5-((3,5-dimethyl-1H-pyrazol-1-yl)methyl)furan-2-carboxylate is added, the mixture is dialyzed with deionized water for 24 hours, and freeze-dried to obtain the furan carboxylic acid imidazolium salt polyionic liquid.

2. The method for preparing a natural rubber material with high tear resistance and high resilience according to claim 1, characterized in that: The raw materials of the natural rubber material are as follows, by weight: 100 parts of natural rubber, 6 parts of activator, 18-30 parts of reinforcing agent, 4-10 parts of paraffin oil, 2-4 parts of antioxidant, 1.5-2.5 parts of dispersed sulfur, 1.1-2 parts of accelerator, and 1-2 parts of silane coupling agent.

3. The method for preparing a natural rubber material with high tear resistance and high resilience according to claim 1, characterized in that: The working conditions for static treatment are: temperature 20-35℃, time 7-9h.

4. The method for preparing a natural rubber material with high tear resistance and high resilience according to claim 1, characterized in that: The antioxidant is prepared by mixing 2-thiol methylbenzimidazole zinc salt and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine in a mass ratio of 1:1; the accelerator is prepared by mixing a thiuram accelerator and a sulfonamide accelerator in a mass ratio of (0.1-0.5): (1-1.5).

5. The method for preparing a natural rubber material with high tear resistance and high resilience according to claim 1, characterized in that: The active agent is prepared by mixing zinc oxide and stearic acid in a mass ratio of 5:

1.

6. The method for preparing a natural rubber material with high tear resistance and high resilience according to claim 1, characterized in that: The active agent is prepared by mixing composite zinc oxide and stearic acid in a mass ratio of 5:

1. The preparation of the composite zinc oxide includes the following steps: (1) Anhydrous ethanol and deionized water are mixed, nano zinc oxide is added, and ultrasonic treatment is performed for 20-30 minutes. A mixed solution of 3-mercaptopropyltriethoxysilane and anhydrous ethanol is added, and the temperature is raised to 45-55° C. and kept warm for 5-6 hours. The mixture is washed and dried to obtain thiolated nano zinc oxide; (2) Under a nitrogen atmosphere, tetrahydrofuran, allyl glycidyl ether and potassium tert-butoxide are mixed, stirred in an oil bath at 58-62°C for 18-20 hours, hydrochloric acid is added, filtered, dialyzed in deionized water and ethanol in turn, and rotary evaporated to obtain an unsaturated polyether skeleton; (3) Mixing terpyridinium chloride hexahydrate, p-toluidine, and N-methylpyrrolidone, adding an unsaturated polyether skeleton and sodium 3-mercapto-1-propanesulfonate, irradiating with light at a wavelength of 450 nm for 7-8 hours, and then dialyzing alternately in deionized water and ethanol, and rotary evaporating to obtain an intermediate preparation; mixing terpyridinium chloride hexahydrate, p-toluidine, and N-methylpyrrolidone, adding the intermediate preparation and thiolated nano zinc oxide, irradiating with light at a wavelength of 450 nm for 7-8 hours, dialyzing in ethanol, and rotary evaporating to obtain polyether anion modified zinc oxide; (4) The polyether anion modified zinc oxide, furan carboxylic acid imidazolium salt polyionic liquid and N-methylpyrrolidone are mixed, ultrasonically stirred for 20-30 minutes, and then kept at 18-25° C. for 2-3 hours, and rotary evaporated to obtain composite zinc oxide.

7. A natural rubber material with high tear resistance and high resilience, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Nano hybrid filler reinforced rubber material and preparation process thereof

    CN111423633A

  • Rubber composition for suspension system of snowmobile and preparation method of rubber composition

    CN113563647A